The Concept of Justice in the Distribution of Inheritance from the Perspective of Islamic Legal Philosophy - Fatimah Zahara; Syahrini Harahap (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
This paper aims to explain the concept of justice in inheritance law from an Islamic perspective. The first knowledge that was lost among Muslims was the knowledge of inheritance, as conveyed by the Prophet Muhammad PBUH. Not only that, there is an attempt to undermine the order of inheritance law in Islam. In the Quran, it is explained that the distribution of inheritance property has 2 provisions, namely mitslu hadzl al-untsayain (two to one) and furudhul al-muqaddarah with numbers 1/2, 1/3, 1/4, 1/6, 1/8, 2/3, this provision is part of the principle of justice. In Islamic legal philosophy, the concept of justice is formulated in maqashid al-syari'ah formulated by al-Syatibi, that the law based on justice is determined by maslahat which is divided into three, namely dharuriyyat, hajiyyat, and tahsiniyyat. This indicates that Islam is very concerned with the issue of justice. The conception of justice will continue to develop in line with social development. This type of research is library research, which is a research that focuses on literature by analyzing the content of some literature related to research from both primary and secondary sources. Then analyze how the concept of justice in the distribution of inheritance from the perspective of Islamic legal philosophy. The result of the discussion is that the meaning of justice in Islamic inheritance law must follow the provisions of Allah swt. not equal distribution. Behind the distribution of inheritance in Islam contains justice that is universal in terms of theology, economics, social, and economic.